2006
DOI: 10.1111/j.1439-0434.2006.01089.x
|View full text |Cite
|
Sign up to set email alerts
|

Components of Resistance to Early Blight in Four Potato Cultivars: Effect of Leaf Position

Abstract: Components of early blight resistance were quantified in leaves of different ages in four potato cultivars. The components of resistance: incubation period (IP), lesion number (LN), early blight severity, lesion expansion rate (LER), latent period (LP) and spore production by lesion area (SPLA), were evaluated separately in the lower, middle and upper leaves of four potato cultivars. Plants of cultivar Aracy (resistant), Delta (moderately resistant), Desire´e (susceptible) and Bintje (susceptible) were inocula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 31 publications
4
29
0
1
Order By: Relevance
“…Previous field evaluations of EB resistance of potato cultivars have used only one or a few epidemiological variables, such as disease severity at any given time during the epidemic (Brune & Reifschneider, 1989;Brune et al, 1990;Christ, 1991;Reifschneider & Brune, 1992;Brune et al, 1994), the AUDPC (Christ, 1991;Dita-Rodríguez et al, 2006;Simon et al, 2009) and r (Holley et al, 1983). Nazareno et al (1999) suggested that caution must be taken if only one epidemiological variable is used during disease assessment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous field evaluations of EB resistance of potato cultivars have used only one or a few epidemiological variables, such as disease severity at any given time during the epidemic (Brune & Reifschneider, 1989;Brune et al, 1990;Christ, 1991;Reifschneider & Brune, 1992;Brune et al, 1994), the AUDPC (Christ, 1991;Dita-Rodríguez et al, 2006;Simon et al, 2009) and r (Holley et al, 1983). Nazareno et al (1999) suggested that caution must be taken if only one epidemiological variable is used during disease assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Potato resistance to EB appears to be associated with cultivar maturity, with the late-maturing cultivars tending to be more resistant than early-maturing cultivars (Douglas et al, 1972;Mendoza et al, 1986;Herriott et al, 1990;Pelletier & Fry 1990;Zhang, 2004;Dita-Rodríguez et al, 2006). However, because EB occurs most often during senescence of the host tissues, some cultivars may appear resistant simply because they are late maturing (Herriott et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Disease severity assessments could was done on lower, middle and upper leaves but middle leaf assay is a useful factor for potato cultivars evaluation [1,6]. Therefore in this research was used from middle leaf for resistance level selection.…”
Section: Disscusionmentioning
confidence: 99%
“…Virus free clones of potato cultivars were obtained from the National plant gene bank of Iran. Six cultivars were conducted Ells, Picasso, Maradona, Marfona, Casmos and Desiree that the cultivar Desiree is used as susceptible reference cultivar when screening potato genotypes in Brazil [6,8]. Plantlets were propagated through nodal cutting and kept in growth chamber at 23˚C ± 2˚C, light with a period of 16 h light and 8 h dark.…”
Section: Plant Materialsmentioning
confidence: 99%
See 1 more Smart Citation